Ownership concentration and risk disclosure quality in the Tunisian context: Evidence from the pre- and during COVID19 periods - Ikhlass Amous; Ahmed Chabchoub (Contabilitate şi Informatică de Gestiune)
Research question: How does ownership concentration impact risk disclosure quality in Tunisian listed companies before and during the Covid19 pandemic, and how does board gender diversity moderate this relationship? Motive: Building mainly on the findings of Haj Salem et al. (2019) who studied the risk disclosure in the tunisian context, this study extends the analysis by investigating the link between risk disclosure quality and the ownership concentration while considering the impact of the Covid19 pandemic. By incorporating board gender diversity as a potential moderating factor, the study provides a more comprehensive understanding of corporate disclosure behavior. Idea: The paper seeks to analyze the link between the ownership concentration and the risk disclosure quality among the Tunisian listed companies while taking into account the effect of the Covid19 pandemic. It also aims at investigating the moderating role of the board gender diversity on the above-mentioned link. Data: Data were collected through content analysis of annual reports of 38 Tunisian listed companies for the period ranging from 2014 to 2021. Tools: The estimation of the studied model was conducted using the xtgls function which allowed the estimation by Generalized Least Squares (GLS) method. Findings: The study revealed a negative impact of the ownership concentration on the risk disclosure quality. As for the moderating impact of the board gender diversity, the results showed a negative and insignificant impact during the first period and a positive and significant impact during the second period. Contribution: This study investigates the relationship between ownership concentration and risk disclosure quality in Tunisia, comparing pre- and during-Covid19 periods. It uniquely explores the moderating role of board gender diversity and contributes to the limited accounting literature on risk disclosure quality.